VD_FINDINFO Jug / 2024 / 522 vom 6. Juni 2024 - VD Tribunal cantonal (2024)
INDEMNITÉEN GÉNÉRAL, REJET DE LA DEMANDE, DÉCISION D'IRRECEVABILITÉ | 382 al. 1 CPP (CH), 406 al. 1 let b CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH), 432 CPP (CH)